2017
DOI: 10.1590/1518-8345.1600.2849
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the culture of safety in public hospitals in Brazil

Abstract: Objective: to assess the culture of safety in three public hospitals.Method: transversal study undertaken in three Brazilian public hospitals, with health professionals through applying the Safety Attitudes Questionnaire (SAQ). Scores greater than or equal to 75 were considered positive.Results: a total of 573 professionals participated in the study, including nurse technicians and auxiliary nurses 292 (51%), nurses 105 (18.3%), physicians 59 (10.3%), and other professionals 117 (20.4%). The mean of the SAQ va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
80
4
59

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(170 citation statements)
references
References 21 publications
27
80
4
59
Order By: Relevance
“…(16) In addition, the factors that contribute to the positive result in this score are: an institution having a favorable working environment, staff satisfied with the work they perform, and, thus, contribution to safety attitudes. (24) When scores are above 80, the results demonstrate a strong consensus among professionals about the safety climate. (22) The teamwork climate in the institutions investigated was positive.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…(16) In addition, the factors that contribute to the positive result in this score are: an institution having a favorable working environment, staff satisfied with the work they perform, and, thus, contribution to safety attitudes. (24) When scores are above 80, the results demonstrate a strong consensus among professionals about the safety climate. (22) The teamwork climate in the institutions investigated was positive.…”
Section: Discussionmentioning
confidence: 88%
“…Authors of this study infer that Brazilian professionals are more satisfied at work compared to professionals from other countries. (24) In this context, professional satisfaction is directly related to the lower occurrence of adverse events, and may influence the safety culture. (16) In addition, the factors that contribute to the positive result in this score are: an institution having a favorable working environment, staff satisfied with the work they perform, and, thus, contribution to safety attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the subject gained the spotlight in 2013 with the creation of the patient safety programme. This programme establishes that the quality of care is only achieved when safety is the fundamental principle managed by institutions (3) . In the care practice, the safety culture is the result of a complex system of policies, programmes, and management support for the workers directly involved with patients to ensure they have the conditions to provide safe care at all stages.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in different Brazilian states using validated instruments revealed weaknesses in assessing the perception of nursing staff of the safety climate (8)(9)(10) . A review of papers on this subject found safety climate assessments in public hospitals (3) , in a private hospital (11) and in public and private hospitals (12) , without correlating the outcomes of these institutions. Therefore, the following question arises: is there a significant difference between the perception of health workers of private and public institutions in relation to the safety climate?…”
Section: Introductionmentioning
confidence: 99%